Validation of Polish Version of Dispositional Flow Scale-2 and Flow State Scale-2 Questionnaires - Józefowicz, Justyna; Kowalczyk-Grębska, Natalia; Brzezicka, Aneta (Frontiers in Psychology, 2022)
The aim of this study is to evaluate the psychometric properties of the Polish version of the Dispositional Flow Scale-2 (DFS-2) and Flow State Scale-2 (FSS-2), for use with Polish adults and young adults. Currently, there are no tools that would allow us to study flow among Polish speakers. At the same time, due to the great interest in flow and its potential importance for effectiveness, cooperation, and learning, it is worth ensuring that reliable validated measurement questionnaires are available for people studying the Polish population. Study participants completed 856 questionnaires, of which 496 individuals (with an average age of 36.31 years) participated in the DFS-2 study and 360 individuals (with an average age of 33.46 years) participated in the FSS-2 study. The maximum likelihood estimator (MLR) was selected for the CFA analysis. Model fit was assessed using: χ2, comparative fit index (CFI), Tucker-Lewis index (TLI), and standardized root mean square of residuals (SRMR) and root mean square of approximation error (RMSEA). For both questionnaires, formative first-level models with nine factors and second-level models with nine factors loaded on a higher-order flow factor were compared using the Satorra-Bentler Scaled difference χ2 test. The ω coefficient was used to estimate the reliability of the FFS-2 and DFS-2 models tested in the CFA method. Confirmatory factor analysis of both DFS-2 structural models showed satisfactory model fit. Most of the fit indices for the hierarchical 2nd order FSS-2 model presented satisfactory values, except for SRMR. Both DFS-2 and FSS-2 factors tested in the analysis showed good reliability (ω ≥ 0.7). Our findings confirmed the reliability and validity of the Polish versions of DFS-2 and FSS-2 scales. The scales are reliable when applied to Polish adults and young adults.